2020
DOI: 10.1038/s41598-020-77493-1
|View full text |Cite
|
Sign up to set email alerts
|

Present value of the Urethral mobility test as a tool to assess Stress urinary incontinence due to Intrinsic sphincteric deficiency

Abstract: Q-tip test offers a simple approach for identifying urethral hypermobility. Considering surgical treatment, stress urinary incontinence (SUI) must be classified and the contribution of intrinsic sphincter deficiency (ISD) and/or urethral hypermobility must be determine. We believe there's a correlation between abdominal leak point pressure (ALPP) and urethral mobility degree, and the aim of this study is to explore it using Q-tip. We conducted a prospective study, between years 2014 and 2016. Females over 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Results demonstrated a 61.75%, 51.61%, and 70.6% agreement between ALPP and urethral mobility (UM), ALPP and composite A (equal to a Q-tip test < 30 • AND ICIQ-SF ≥ 10 points), and ALPP and composite variable B (equal to low urethral mobility, AND/OR hypoestrogenism, AND/OR history of radiotherapy, AND/OR previous pelvic surgery), respectively. The authors found that neither the degree of UM, nor the composite variables, correlated or agreed with urethral function tests in UDS, which suggested that the ALPP cannot be predicted using the Q-tip test or the ICIQ-SF for classifying patients with SUI [29]. However, Ohter study in 2022 intended to evaluate the use of transperineal ultrasonography while diagnosing SUI by comparing the urethral angle (α), posterior urethrovesical angle (β), and bladder-neck descent (BND) during rest and Valsalva maneuver in continent women and women with SUI.…”
Section: Discussionmentioning
confidence: 95%
“…Results demonstrated a 61.75%, 51.61%, and 70.6% agreement between ALPP and urethral mobility (UM), ALPP and composite A (equal to a Q-tip test < 30 • AND ICIQ-SF ≥ 10 points), and ALPP and composite variable B (equal to low urethral mobility, AND/OR hypoestrogenism, AND/OR history of radiotherapy, AND/OR previous pelvic surgery), respectively. The authors found that neither the degree of UM, nor the composite variables, correlated or agreed with urethral function tests in UDS, which suggested that the ALPP cannot be predicted using the Q-tip test or the ICIQ-SF for classifying patients with SUI [29]. However, Ohter study in 2022 intended to evaluate the use of transperineal ultrasonography while diagnosing SUI by comparing the urethral angle (α), posterior urethrovesical angle (β), and bladder-neck descent (BND) during rest and Valsalva maneuver in continent women and women with SUI.…”
Section: Discussionmentioning
confidence: 95%
“…ALPP < 60 cm H2O meaning the diagnostic value of type III SUI (ISD), an ALPP between (90-120) cm H2O is considered diagnostic of type II SUI (HMU), while ALPP between (60-90) cm H2O indicate the presence of both type II and type III . 12 Detrusor instability is diagnosed when the true detrusor pressure increased or even when smaller increases cause urgency or incontinence during urodynamic. 13 Mixed urinary incontinence" (stress and urge) is a combination of urodynamic conditions (urodynamic stress incontinence and detrusor over activity) in the same individual .…”
Section: Methodsmentioning
confidence: 99%